Let's sign (New York, NY : St. Martin's Press ; [S.l.] : Priddy Books, 2008)
Incorporating signs based on American Sign Language, this book is for parents and infants to use together, to "communicate with your baby before they can speak"--P. [4] of cover. 32 flash cards for use in practicing the signs are stored in a container mounted on the book.
Cover title.
Keywords: Board books; Infants -- Language -- Juvenile literature; Nonverbal communication in infants -- Juvenile literature; Sign language -- Juvenile literature